Association between the Dietary Inflammatory Index with gallstone disease: finding from Dena PERSIAN cohort - Zeinab Sadri; Javad Harouni; Farhad Vahid; Zohreh Khosravani; Fereshteh Najafi (BMJ Open Gastroenterology)
Objective The Dietary Inflammatory Index (DII) is a documented nutritional tool for assessing diet-induced inflammation that has been linked to various diseases/outcomes. The association between DII and gallstone disease (GSD) is yet to be explored. The objective of this study was to examine the association between DII and GSD.Design This cross-sectional study was conducted using the baseline phase data of the Dena PERSIAN cohort. The analysed data included demographic information, lifestyle variables, body mass index, diabetes and fatty liver history, and laboratory test results. The 113-item Food Frequency Questionnaire was used to estimate the dietary intake of participants and quantify the inflammatory potential of the individual’s diet. DII score was analysed as a continuous and quartiles variables. Univariable and multivariate logistic regressions were used to investigate the relationship between GSD and DII scores .Results Out of 3626 individuals entering the study, 173 (4.77%) had GSD. The median DII was −0.08 (IQR=0.18). In the unadjusted model, the odds of having GSD were significantly higher in the first and second quartiles of DII (anti-inflammatory diet) than in higher quartiles (proinflammatory diet). In the adjusted model, the odds of having GSD in the third and fourth quartiles of DII scores compared with the first quartile were OR=0.59 (95% CI 0.36 to 0.95) and OR 0.51 (95% CI 0.30 to 0.84), respectively.Conclusion The results of this study suggest that a proinflammatory diet is associated with a reduced chance of GSD. However, longitudinal studies are needed to examine the causal association.